City silhouette, world climate - Kristof Dascher (European Regional Science Association (ERSA), 2013)
Global emissions of carbon dioxide need to fall lest climate change will accelerate. Any effective climate policy must raise the price of carbon consumption. From an urban perspective, one desirable effect of a carbon tax would be to induce households to move closer to where they work. This paper shows that: If the initial distribution of commuting distances (the city silhouette) is skewed towards the periphery then a carbon tax will leave resident landlords better off - even if these landlords need to shoulder those extra commuting costs themselves, too. If resident landlords are decisive then this insight provides an urban silhouette based explanation of why some governments appear so much more willing to confront their citizens with the true cost of emitting carbon dioxide than others. More briefly, the paper suggests a connection between urban form and climate politics.
Keywords: 330; Climate Change; Political Economy; Commuting Costs; Rents; Closed City